Contract-based slicing helps on safety reuse - Areias, Sérgio (2010)
In this poster we describe a work in progress aimed at using a variant of specification-based slicing to improve the reuse of annotated software components, developed under the so called design-by-contract approach. We have named this variant as contract-based because we use the annotations, more precisely the pre and post-conditions, to slice programs intra and inter-procedures. The idea, expressed in the poster, is to take the pre-condition of the reused annotated component as slicing criterion, and slice backward the program where the component is called. In that way, we can isolate the statements that have influence on the variables involved on the pre-condition and check if it is preserved by that invocation, or not.